Typology of Filipino female superintendent leadership - Roque, Eleanor Soledad Vinson (2006)
Females in the administrative role demonstrate a wide variety of leadership behaviors and make unique leadership choices. The study described and compared the leadership behaviors of Filipino superintendents with their male counterparts. A self-constructed survey questionnaire and the Multifactor Leadership Questionnaire were used to gather data. Although both cexes exhibit transformatinal leadership behavior, women were more transformational compared to men. Women reflected more of the contingent reward or reinforcement dimension of transactional leadership and were receptive to innovations. They attributed their success to personal assets like love and commitment to the work, hard work, determination, knowledge of the curriculum, higher educational attainment, confidence, and satisfaction of their teachers' and students' needs.
Vita.
Thesis (Ph. D. Educational Administration)--University of the Philippines, Diliman.
Keywords: Women school superintendents -- Philippines; Educational leadership -- Philippines; Leadership -- Ability testing -- Philippines; Leadership in women -- Philippines; School superintendents -- Philippines